Skrining Aktivitas Antibakakteri Fraksi Kulit Buah Durian (Durio zibhetimus M) - Kemal, Amir (Journal of Pharmacy Tiara Bunda, 2023)
A screening study of antibacterial activity of Durio zibethinus M fraction on Escherhicia coli bacteria and Staphylococcus aureus bacteria has been carried out. This study aims to determine the inhibitory effect of durian peel extract on Escherhicia coli bacteria and Staphylococcus aureus bacteria, to determine the most active fraction in inhibiting the growth of Escherhicia coli bacteria and Staphylococcus aureus bacteria and to find out the most active class of compounds against antibacterial activity.The fraction on Duiro zibethinus M was carried out by vacuum liquid chromatography method..Ethyl acetate and methanol extract have antibacterial activity characterized by the presence of clear inhibition zones in the paper disk area, for n-hexane extract does not have a inhibitory effect on bacteria. The results of the inhibition of ethyl acetate extract, which is 17.13 mm are strongly marked for Escherichia coli bacteria and moderate inhibitory capacity of 7.34 mm for Staphylococcus aureus bacteria. Whereas the inhibitory results of methanol extract were 15.11 mm which means that it is strong for Escherichia coli bacteria and strong inhibition power of 11.45 mm for Staphylococcus aureus bacteria. Fraction 2 has antibacterial activity in Staphylococcus aureus bacteria characterized by the presence of clear inhibition zones in the piper disk area, whereas in Escherichia coli bacteria there is no inhibiting fraction. The results of the inhibition of fraction 2 is 9.96 mm which means that it is medium for Staphylococcus aureus bacteria. On the results of identification fractionation of Durio zibethunus M fruit skin showed function as an antibacterial, namely the Flavonoid compound